2021
DOI: 10.1038/s41598-021-87457-8
|View full text |Cite
|
Sign up to set email alerts
|

Low biological fluctuation of mitochondrial CpG and non-CpG methylation at the single-molecule level

Abstract: Mammalian cytosine DNA methylation (5mC) is associated with the integrity of the genome and the transcriptional status of nuclear DNA. Due to technical limitations, it has been less clear if mitochondrial DNA (mtDNA) is methylated and whether 5mC has a regulatory role in this context. Here, we used bisulfite-independent single-molecule sequencing of native human and mouse DNA to study mitochondrial 5mC across different biological conditions. We first validated the ability of long-read nanopore sequencing to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…On the one hand, there is evidence for a negative association between mtDNA methylation and gene expression (Sirard, 2019 ) and our results may indicate a higher expression of mtDNA genes in neuron-derived DNA. On the other hand, a previous study reported lower mtDNA CpG methylation levels in cell lines compared to tissue-derived DNA (Goldsmith et al, 2021 ). When exploring iPSC-derived midbrain neurons, lower CpG mtDNA methylation was detected compared to blood and perhaps the reprogramming process also modifies the epigenetics of mtDNA.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…On the one hand, there is evidence for a negative association between mtDNA methylation and gene expression (Sirard, 2019 ) and our results may indicate a higher expression of mtDNA genes in neuron-derived DNA. On the other hand, a previous study reported lower mtDNA CpG methylation levels in cell lines compared to tissue-derived DNA (Goldsmith et al, 2021 ). When exploring iPSC-derived midbrain neurons, lower CpG mtDNA methylation was detected compared to blood and perhaps the reprogramming process also modifies the epigenetics of mtDNA.…”
Section: Discussionmentioning
confidence: 84%
“…To adjust the detected methylation frequency of the blood- and neuron-derived samples, we calculated the false-positive rate (FPR = Number of called methylated cytosines/Number of all called cytosines) as recommended (Goldsmith et al, 2021 ) from the long-range PCR products. The resulting FPR of Nanopolish and Megalodon for blood- and neuron-derived DNA was subtracted from the methylation frequency of each site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors suggested that mtDNA methylation in the gene bodies promoted the expression of the genes, presumably by affecting the post-transcriptional modifications of polycistronic mitochondrial mRNAs, since in one cell culture, they found hypermethylation of MT-CO1 and MT-CYB genes with concomitant high expression levels [ 74 ]. By using the same technique, increased CpG and CpH mtDNA methylation levels have been observed in head and neck tumor samples when compared to their matched adjacent normal tissues [ 75 ].…”
Section: Altered Mtdna Methylation and Human Diseasesmentioning
confidence: 99%
“…Moreover, a study investigating mtDNA methylation in human cells by means of a third-generation sequencing platform, namely, the nanopore sequencer (MinION, Oxford Nanopore), which is a high-throughput nanopore-based single-molecule device that can directly sequence the entire mtDNA molecule, minimizing potential nucleotide errors introduced by PCR amplification, and preserving epigenetic modifications by avoiding the use of bisulfite treatment, revealed clearly detectable levels of mtDNA methylation [ 74 ]. Likewise, by using high-coverage nanopore sequencing at the single-molecule level, mtDNA methylation was recently investigated in different sample types and biological conditions [ 75 ]. Methylation was overall higher in tissues compared to cell lines, and despite that mtDNA methylation levels were generally low, global and single-base differences were found between cancer tissues and the adjacent healthy tissues.…”
Section: Debate On the Existence And Function Of Mtdna Methylationmentioning
confidence: 99%